Identities in Translation: Management Concepts as Means and Outcomes of Identity Work. Issue 6 (June 2020) - van Grinsven, Marlieke; Sturdy, Andrew; Heusinkveld, Stefan
This article seeks to develop our understanding of how management concepts are translated by examining the role of identity work in this process. Rather than a sole focus on changes in a management concept, we examine tensions and congruences between agents' orientations towards that concept and how they see the broader organizational engagement with it. Through an examination of qualitative data from a study of those specifically tasked with the implementation of Lean in hospital contexts, we identify their narratives of self in relation to the concept. We show how, through four different types of translation-as-identity-work – externalizing, professionalizing, rationalizing and proselytizing – both the concept and the agent are constructed simultaneously. In recognizing interconnectedness, diversity and dynamism in these actors' involvement, we seek to integrate, contextualize and broaden existing perspectives on agency in translation research.